A Prognostic Pyroptosis-Related lncRNAs Risk Model Correlates With the Immune Microenvironment in Colon Adenocarcinoma - Xia, Fada; Yan, Yuanliang; Shen, Cong (Frontiers in Cell and Developmental Biology, 2021)
Recent studies indicated that long non-coding RNAs (lncRNAs) might participate in the regulation of tumor cell proptosis. However, the connection between the expression of lncRNAs and pyroptosis was remain unclear in colon adenocarcinoma (COAD). This study aims to explore and establish a prognostic signature of COAD based on the pyroptosis-related lncRNAs. We identified 15 prognostic pyroptosis-related lncRNAs (ZNF667-AS1, OIP5-AS1, AL118506.1, AF117829.1, POC1B-AS1, CCDC18-AS1, THUMPD3-AS1, FLNB-AS1, SNHG11, HCG18, AL021707.2, UGDH-AS1, LINC00641, FGD5-AS1 and AC245452.1) from TCGA-COAD dataset and used them to construct the risk model. After then, this pyroptosis-related lncRNA signature was validated in the patients from GSE17536 dataset. The COAD patients were divided into low-risk and high-risk groups by setting the median risk score as the cutoff point and showed differences in immune microenvironment. Hence, we constructed the immune risk model based on the infiltration levels of ssGSEA immune cells. Interestingly, risk model and immune risk model were all the independent prognostic risk factors. Therefore, a nomogram combined risk score, immune risk score and clinical information meaningful in univariate and multivariate Cox regression analysis was established in predicting overall survival (OS) of COAD patients. In general, the signature consisted of 15 pyroptosis-related lncRNAs and was proved to be associated with the immune landscape in COAD patients.